PERTIMBANGAN BADAN PENGUSAHAAN BINTAN MENARIK INVESTOR SINGAPURA PADA BIDANG PARIWISATA - ', Nurhayati; Iskandar, Irwan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
Free Trade Zone (FTZ) is a free trade and port that has been regulated by the government in law number 36 of 2000, Government Regulation of the Republic of Indonesia number 47 of 2007 and Government Regulation number 41 of 2021. The existence of FTZ with the aim of utilizing areas that have great potential to develop and include foreign investment for regional development to be more advanced and better. The strategic geographical location of BP Bintan is close to Singapore and Malaysia. FTZ BP Bintan has 4 areas, Bintan is famous for its beautiful tourism and the biggest income also comes from tourism, the international tourism area is in North Bintan which is purely managed by Singapore through PT. Bintan Resort Cakrawala (BRC). This research uses the perspective of Neoliberalism and the theory of Foreign Direct Investment (FDI) with nation state analysis using qualitative methods, with primary and secondary data collection techniques, namely observation techniques, interviews, written documents, reports, journals, or other official documents. The result of this writing is an increase in the welfare of the recipient country with a link to new innovations, new technology, increased employment, increased capital, and job development in Bintan Regency. The result of this writing is an increase in welfare in the recipient country with the linkage of new innovations, namely the development of blood innovation, new technology with the existence of KI Bintan Aerospes which supports technology, increasing employment opportunities with developments such as hotels, villas, resorts, restaurants and others to increase employment, increasing capital increase capital continues to increase growth by 6.14% in 2023, and developing employment opportunities in Bintan Regency. Keywords: Free Trade Zone (FTZ), Foreign Direct Investment (FDI), Tourism.